2018
DOI: 10.19047/0136-1694-2018-95-71-89
|View full text |Cite
|
Sign up to set email alerts
|

Changes in C : N : Р Ratios in Plant Biomass, Soil and Soil Microbial Biomass Due to the Warming and Dessication Effect of Flaring

Abstract: Climate warming results in significant changes in the structure and functioning of terrestrial ecosystems. The ecosystems situated near oil-well gas flares may be used as model ones for studying warming effect on soil and vegetation. By contrast to regular manipulation experiments where ecopysiological factors are modified or controlled artificially, we used anthropogenically affected condi-tions caused by the gas flaring. Our research was aimed to assess the warming and desiccation effect on the stoichiometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…They also suggest that low soil N and P concentrations tend to be associated with higher temperatures along natural long‐term climatic gradients, but the reverse occurs for phenotypic responses of species to N in short‐term field studies with climatic manipulation (Yuan et al, ). Several studies have indeed reported decreases in aboveground plant N:P ratios under warming that were attributed to the greater allocation of P to stems and/or to greater plant growth capacity (Dudareva, Kvitkina, Yusupov, & Yevdokimov, ; Wang, Ciais, et al, ; Wang, Liu, et al, ). The effects of warmer temperatures on plant and soil C:N:P ratios along natural gradients are not easy to distinguish from those of precipitation, radiation, or atmospheric N deposition, which frequently correlate with the geographical temperature gradient (Jiao et al, ).…”
Section: Shifts In N:p Ratios Mediated By Anthropogenic Drivers Of Glmentioning
confidence: 99%
“…They also suggest that low soil N and P concentrations tend to be associated with higher temperatures along natural long‐term climatic gradients, but the reverse occurs for phenotypic responses of species to N in short‐term field studies with climatic manipulation (Yuan et al, ). Several studies have indeed reported decreases in aboveground plant N:P ratios under warming that were attributed to the greater allocation of P to stems and/or to greater plant growth capacity (Dudareva, Kvitkina, Yusupov, & Yevdokimov, ; Wang, Ciais, et al, ; Wang, Liu, et al, ). The effects of warmer temperatures on plant and soil C:N:P ratios along natural gradients are not easy to distinguish from those of precipitation, radiation, or atmospheric N deposition, which frequently correlate with the geographical temperature gradient (Jiao et al, ).…”
Section: Shifts In N:p Ratios Mediated By Anthropogenic Drivers Of Glmentioning
confidence: 99%
“…A meta-analysis of 86 studies that did not differentiate among plant organs found an overall increase in N:P ratios along natural temperature gradients, but not in field experiments with controlled warming conditions (Yuan and Chen, 2015). Several studies have reported a decrease in aboveground plant N:P ratios under warming, which were attributed to a greater allocation of P to stems and/or to a greater capacity for plant growth (Dudareva et al, 2018;Wang et al 2018e, 2019b. A meta-analysis of data from 76 warming manipulation field studies reported an overall increase in plant N:P ratios under warming (Yue et al, 2017).…”
Section: Key Trade-offs and Feedbacks Between Drivers Of Global Envir...mentioning
confidence: 99%